Effect of aeration rate on the performance of intermittently aerated constructed wetland - Queluz, João Gabriel Thomaz [UNESP]; Yabuki, Lauren Nozomi Marques [UNESP]; Garcia, Marcelo Loureiro [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
The aim of the present work was to evaluate the effect of different aeration rates on the removal of total nitrogen (TN) and chemical oxygen demand (COD) in intermittently aerated horizontal subsurface flow constructed wetlands (HFCW). Four pilot-scale HFCWs were evaluated using different aeration rates (0, 2, 5, and 10 L min-1) with a fixed intermittent aeration interval of 3 h d-1 (1 h with aeration 7 h without aeration). The HFCWs received 8.6 L d-1 of synthetic effluent, resulting in a hydraulic retention time of 3 days. The results show that intermittently aerated HFCWs were highly efficient in removing COD (>97%), TN (>80%) and NH4+ (>97%), while the HFCW without aeration showed lower efficiencies in the removal of COD (93.9%), TN (48.8%), and NH4+ (57.7%). In addition, the results also show that the three intermittently aerated HFCW achieved similar performance in the removal of COD, TN, and NH4+. Finally, the results indicate that intermittent aeration allows the simultaneous occurrence of nitrification and denitrification, thus improving the performance of HFCW in removing TN. However, the use of different aeration rates does not alter COD and TN removal efficiencies.
Efeito Da Taxa De Aeração No Desempenho De Alagados Construídos Aerados Intermitentemente
Keywords: Artificial aeration; COD removal; The nitrogen removal